(untitled) (Cadernos de Sociomuseologia, 2017)
Sports museums are attentive to contemporary social concerns and issues relevant to plural societies, which guide the adoption of the museum by inclusive strategies and new museum languages, in order to involve communities by giving them a sense of participation in the processes of cultural and identity representation. Since football is a cultural production of a time, of from now, or for a specific social formation, we can question the position of these museums within the scope of sociomuseology. In other words, we may begin by questioning whether the ethos of football museums embody the social dimension produced, or whether this dimension is inherent in the museological discourses conceived and evoked. From the Trophy Rooms to the current Football Museums, we reflect on the permanent challenges to the redefinition of museological thought and the knowledge of its dynamics. Our research project privileges the permanent dialogue with the theme, problems and hypotheses demarcated by the social concepts that sustain the museological action in these museums, such as the concepts of identity and memory. Processes that arise structured on the construction of identity representations in the football. Keywords: Identity; Memory; Sociomuseology; Sports Museums; Football